SOCIALIZATION OF CHILDREN'S RIGHTS AS A PREVENTIVE EFFORTS OF CHILD BULLYING AT THE NUR KAROMAH ORPHANAGE DEPOK - Zebua, Winda Dwi Astuti; Kurniawan, Donny; Sabilla, Mizna; Alfatah, Rivan (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
Bullying is still an important issue that needs serious handling, especially involving children as both perpetrators and victims. The impact of bullying is very detrimental to children, reducing self-confidence, fear that it can lead to suicidal behavior or physical violence. Therefore, it is felt that this socialization activity on children's rights needs to be carried out as an effort to prevent bullying among the children of Panti Nur Karomah Depok. The method used in this activity consists of five stages, namely situation analysis, internal partner analysis, goal setting, implementation and evaluation. In implementing activities, the delivery of material uses video media and pictorial material that is interesting to children. The presentation of the material was also followed by games and questions and answers so that participants were more enthusiastic and active in participating in the activity. The results of this activity were less than 50% of participants taking the pretest, but all pretest participants answered that they had laughed at their friends. Some of them thought that it was just a joke, because they didn't know what they were doing, it could be considered nonverbal bullying.